2016
DOI: 10.21873/anticanres.11037
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of TMPRSS2-ERG Fusion Gene in Prostate Cancer

Abstract: A combination of high preoperative serum PSA and high expression of TMPRSS2-ERG could be promising in distinguishing those tumors that are aggressive and life-threatening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…[1,3] The prognostic and predictive value of TMPRSS2-ERG fusions is still under active investigation; however, some studies have suggested an association of the fusion gene with higher recurrence risk and possibly even increased risk of prostate cancer-related death. [4-6]…”
Section: Introductionmentioning
confidence: 99%
“…[1,3] The prognostic and predictive value of TMPRSS2-ERG fusions is still under active investigation; however, some studies have suggested an association of the fusion gene with higher recurrence risk and possibly even increased risk of prostate cancer-related death. [4-6]…”
Section: Introductionmentioning
confidence: 99%
“…For PCa, carcinogenesis and the mechanisms affecting the progression and prognosis are multistep processes [21]. Although the previous reports have shown that many factors including lncRNA HCG11, miR-129, as well as TMPRSS2-ERG fusion gene have affected the development and prognosis of PCa [22][23][24], the prediction and diagnosis of PCa patients was still poor. Thus it is important to nd a novel biomarker to improve the diagnostic e ciency of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…72 ERG rearrangements and over-expression define the largest of the molecular classes of PC based on molecular oncogenic drivers and has been repeatedly associated with accelerated disease progression and worse prognosis. 73-74 More recently, many reports have correlated response to treatment to ERG expression, which became a compelling biomarker to investigate clinically.…”
Section: Ctc As Source Of Tumor Tissue For Biomarker Investigationmentioning
confidence: 99%